Competitiveness and trade potential of India’s dairy industry - Rakotoarisoa, Manitra A.; Gulati, Ashok (Elsevier, 2006)
India has become the world’s largest milk producer but its dairy industry lacks market access. This paper determines how world dairy policy reforms would affect dairy production and trade in India and the competitiveness of its dairy industry. We measure nominal protection coefficient for India’s dairy products to determine level and change in competitiveness between 1975 and 2001. We estimate parameters of domestic demand for and supply of raw milk and whole milk powder to determine how a world price increase would affect domestic milk production and whole milk powder exports. Results show that India’s dairy products lack export competitiveness. But with less distorted world dairy markets, India could be competitive and would emerge as a net exporter of whole milk powder, benefiting dairy industries and milk producers in India.